Mutational landscape reflects the biological continuum of plasma cell dyscrasias - Rossi, Alessandra; Hegenbart, Ute (Blood cancer journal, 2017)
We subjected 90 patients covering a biological spectrum of plasma cell dyscrasias (monoclonal gammopathy of undetermined significance (MGUS), amyloid light-chain (AL) amyloidosis and multiple myeloma) to next-generation sequencing (NGS) gene panel analysis on unsorted bone marrow. A total of 64 different mutations in 8 genes were identified in this cohort. NRAS (28.1%), KRAS (21.3%), TP53 (19.5%), BRAF (19.1%) and CCND1 (8.9%) were the most commonly mutated genes in all patients. Patients with non-myeloma plasma cell dyscrasias showed a significantly lower mutational load than myeloma patients (0.91±0.30 vs 2.07±0.29 mutations per case, P=0.008). KRAS and NRAS exon 3 mutations were significantly associated with the myeloma cohort compared with non-myeloma plasma cell dyscrasias (odds ratio (OR) 9.87, 95% confidence interval (CI) 1.07-90.72, P=0.043 and OR 7.03, 95% CI 1.49-33.26, P=0.014). NRAS exon 3 and TP53 exon 6 mutations were significantly associated with del17p cytogenetics (OR 0.12, 95% CI 0.02-0.87, P=0.036 and OR 0.05, 95% CI 0.01-0.54, P=0.013). Our data show that the mutational landscape reflects the biological continuum of plasma cell dyscrasias from a low-complexity mutational pattern in MGUS and AL amyloidosis to a high-complexity pattern in multiple myeloma. Our targeted NGS approach allows resource-efficient, sensitive and scalable mutation analysis for prognostic, predictive or therapeutic purposes.
Gesehen am 24.04.2018